Symmetric dimethylarginine and renal function analysis in horses with dehydration. (3rd August 2021) - Lo, Hsiao‐Chien; Winter, Judith C.; Merle, Roswitha; Gehlen, Heidrun
Abstract: Background: Acute dehydration caused by a variety of diseases in horses can lead to acute kidney injury. However, current renal biomarkers usually indicate renal damage late in the course of the disease. A novel biomarker would be helpful to diagnose renal disease earlier. Objectives: (1) To estimate the correlation of serum symmetric dimethylarginine (SDMA) concentrations with the degree of dehydration, traditional renal biomarkers and renal function analysis, and (2) to determine the value of SDMA as a prognostic and early biomarker of renal injury in horses. Study design: Prospective cohort. Methods: Serum SDMA, creatinine and urea concentrations and renal function analysis were measured in 41 horses with dehydration at 4 time points until 48 h after admission. Horses were grouped according to their dehydration level into mildly, moderately and severely dehydrated groups. Results: Serum SDMA concentrations at admission correlated with creatinine concentrations ( r  = .412, P  < .001). Differences in SDMA concentrations at admission were detected among dehydration levels but not between survivors and nonsurvivors. Significant correlations of SDMA concentrations with other markers of renal function analysis and short‐term outcome were not observed. Main limitations: Besides the small sample size and low statistical power, missing urine samples at specific time points were also 1 of the main limitations. Only 1 of the horses developed acute kidney injury, which made the evaluation of the predictive value of SDMA difficult. Conclusions: SDMA concentrations correlated significantly with creatinine concentrations in dehydrated horses. Further research is needed to reveal the application of SDMA in horse.